Salt resistance strategies of amaranth salt-resistant mutant lines - ATOU, Richard; TONOUEWA, Gauthier; Wouyou, Agapit; KPOCHEME, Eustache; Missihoun, Antoine Abel; Ahoton, Léonard E; AGBANGLA, CLÉMENT; LUTTS, Stanley; GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD (My University, 2023)
Improving plant salt tolerance is thus a veritable challenge for breeders as salt stress is one of the most important factors that negatively affect plant growth and productivity worldwide. In this study, we evaluated the physiological strategies involved in the salt resistance of three salt resistant mutant lines. Three weeks old plants of the three mutant lines and that of the control cultivar Locale were submitted in pots to three NaCl concentrations (0; 100 and 200 mM) in a completely randomized design with three replications. Plant growth, ions and organic solutes contents were determined after two weeks of treatment. Plant growth reduction under salt stress was earlier and more accentuated in the control cultivar followed by line L2 than the salt resistant lines L18 and L23. The rate of Na+, proline and soluble sugars accumulation; that of K+ and Ca++ absorption and that of K/Na and Ca/Na reduction under salt stress varied greatly according to the population. The salt resistance of line L18 was due to Na+ accumulation in leaves associated to proline and soluble sugars accumulation, the maintenance of high absorption of Ca++, high K/Na and Ca/Na ratios whereas that of line L23 was due to Na+ exclusion from leaves associated to the maintenance of high absorption of high K+ and Ca++, high K/Na and Ca/Na ratios. Line L2 resist to salt stress via proline accumulation and the maintenance of high Ca/Na ratio. Thus, lines developped different salt resistance strategies according to their relative salt resistance level.
Keywords: Amaranthus cruentus; mutant lines; salt resistance mechanisms